Traditional knowledge of plants used in hunting and fishing practices among Baka hunter-gatherers of eastern Cameroon - Evariste Fedoung Fongnzossie; Marlène Tounkam Ngansop; Takanori Oishi; Achille Bernard Biwole; Elvire Hortense Biye; Mitsuo Ichikawa (BMC, 2023)
Abstract Background Baka hunter-gatherers have a well-developed traditional knowledge of using plants for a variety of purposes including hunting and fishing. However, comprehensive documentation on the use of plants for hunting and fishing in eastern Cameroon is still lacking. Method This study aimed at recording plants used for hunting and fishing practices, using focus group discussion, interviews and field surveys with 165 Baka members (90 men and 75 women) of different age groups in 6 villages. Results The most frequent techniques used for hunting and fishing are the use of animal traps, fishing lines, dam fishing, hunting with dogs and spear hunting. We recorded a total of 176 plant species used in various hunting practices, the most frequently cited one being Zanthoxylum gilletii (De Wild.) P.G.Waterman, Greenwayodendron suaveolens (Engl. & Diels) Verdc., Microcos coriacea (Mast.) Burret, Calamus deërratus G.Mann & H.Wendl. and Drypetes sp. These plants are used for a variety of purposes, most frequently as hunting luck, psychoactive for improving the dog's scent and capacity for hunting, materials for traps, and remedies for attracting animals and for making the hunter courageous. Conclusion Plants used for hunting purposes here are embedded in a complex ecological and cultural context based on morphological characteristics, plant properties and local beliefs. This study provides a preliminary report and leaves room for further investigations to improve the documentation of the traditional knowledge systems of the studied community.